Application of LCâMS/MS for quantitative analysis of glucocorticoids and stimulants in biological fluids - Jamshed Haneef; Mohammad Shaharyar; Asif Husain; Mohd Rashid; Ravinesh Mishra; Shama Parveen; Niyaz Ahmed; Manoj Pal; Deepak Kumar (Elsevier, 2013)
Liquid chromatography tandem mass chromatography (LCâMS/MS) is an important hyphenated technique for quantitative analysis of drugs in biological fluids. Because of high sensitivity and selectivity, LCâMS/MS has been used for pharmacokinetic studies, metabolites identification in the plasma and urine. This manuscript gives comprehensive analytical review, focusing on chromatographic separation approaches (column packing materials, column length and mobile phase) as well as different acquisition modes (SIM, MRM) for quantitative analysis of glucocorticoids and stimulants. This review is not meant to be exhaustive but rather to provide a general overview for detection and confirmation of target drugs using LCâMS/MS and thus useful in the doping analysis, toxicological studies as well as in pharmaceutical analysis. Keywords: LCâMS/MS, Ionization techniques, Glucocorticoids, Stimulants, Hyphenated techniques, Biological fluid